Calcareous Till Facies North of Lake Superior, Ontario: Implications for Laurentide Ice Streaming - Hicock, Stephen (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1988)
ABSTRACTIn the Geraldton and Hemlo areas distantly-derived carbonate tills lie between slightly to non-calcareous tills and can be distinguished by textural, carbonate, and clast compositions. Their occurrence and uniform character over large areas of the Shield attest to high sediment flux by rapid movement of distal debris within the southern part of the Laurentide Ice Sheet. This is consistent with low surface profiles reconstructed for the Superior and Michigan lobes which were likely fed by ice north of Superior and probably affected by ice streaming. Till deposition in the Geraldton and Hemlo areas can be explained with one southwestward glacial advance. A broad ice stream probably issued out of James Bay and up the Albany conduit between zones of normal ice velocity within the Laurentide marginal area. It may have split to flow down the Drowning and Kenogami troughs. Eventually, zones of ice streaming reached the Geraldton and Hemlo areas where Shield uplands induced lee side extending flow, downward transport, and lodgment of calcareous englacial debris on local tills. Following the glacial maximum much of the distal englacial debris was laid down by subglacial meltout. However, a glacial reactivation occurred which moulded drumlins in the carbonate tills near Geraldton and deposited an upper calcareous lodgment till at Hemlo. Final Laurentide decay resulted in meltout of supraglacial debris that had been sheared up to or near the glacier surface from the stoss sides of the uplands.